1991
DOI: 10.3109/00016489109137418
|View full text |Cite
|
Sign up to set email alerts
|

Vocal Fold Fixation in Laryngeal Carcinomas

Abstract: The mechanisms of vocal fold fixation were determined by means of a whole-organ serial section study. A total of 80 laryngectomy specimens, 36 supraglottic and 44 glottic carcinomas, was investigated. In the supraglottic carcinomas, the most frequent cause of fixation of the ipsilateral vocal fold was a deep massive tumor invasion in the arytenoid eminence and the second most frequent cause was an extensive involvement of the thyroarytenoid (TA) muscle. Fixation of the contralateral vocal fold resulted from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 5 publications
3
19
0
Order By: Relevance
“…18 In the present series, all 16 patients with cT2 cancer had an impaired vocal cord mobility with a normal arytenoid mobility, and TA muscle infiltration was found in nine of them (56%). As long as the disease is limited to the TA ligament, vocal cord mobility does not change substantially, whereas any invasion of the TA muscle is likely to be associated with a mobility impairment.…”
Section: Discussionsupporting
confidence: 44%
“…18 In the present series, all 16 patients with cT2 cancer had an impaired vocal cord mobility with a normal arytenoid mobility, and TA muscle infiltration was found in nine of them (56%). As long as the disease is limited to the TA ligament, vocal cord mobility does not change substantially, whereas any invasion of the TA muscle is likely to be associated with a mobility impairment.…”
Section: Discussionsupporting
confidence: 44%
“…The use of SCL in the treatment of tumors causing cord fixation has decreased the number of total laryngectomy and near-total laryngectomy procedures in our practice. Based on the evaluation of 80 laryngectomy specimens, Hirano et al [7] determined that the most common reasons for cord fixation were the extensive invasion of the thyroarytenoid muscle in glottic tumors and deep massive tumor invasion of the Fig. 1 Overall survival rate after supracricoid laryngectomy with cricohyoidopexy Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, on analysis of 23 larynx with serious true vocal cord fixation, Kirchner and Som 8 found that the neoplastic invasion was limited to the paraglottic area and had not invaded the cricoid or thyroid cartilage. On the other hand, Olofsson et al 9 and Hirano et al 10 observed an invasion of the thyroarytenoid muscle in their anatomopathologic studies on all cases of true vocal cord fixation. In these particular clinicopathologic cases, other authors used vertical surgery, resulting in relapse in from 9% to 46% of the patients.…”
Section: Discussionmentioning
confidence: 99%